Adoption of Self Check-In Services at Terminal 1A of Soekarno-Hatta International Airport - Rully Setyawan; Yuliantini Yuliantini; Endang Sugiharti; Lira Agusinta; Zaenal Abidin (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The provision of Self-service Check -in facilities at Terminal 1A is expected to improve operational smoothness, especially to automate the Check -in process using technology so that it can be more effective and efficient. This study was conducted to highlight the adoption of the use of Self-service Check -in facilities, using qualitative descriptive methods and analysis using the Delphi method. The purpose of the study is in line with the formulation of the problem and research questions, with the conclusion that Self-service Check -in facilities can improve service quality because they can be used easily, practically and save time in the Check -in process. Data were obtained through direct observation, interviews, documentation, and literature studies. The findings show that Self-Check -in facilities can also reduce the burden on officers and queues in carrying out the Check -in process at manual counters, but these facilities are not optimal because there are still network constraints or paper that does not come out to print boarding passes, and has not been integrated with Self-baggage drop. Several efforts have been made to overcome these obstacles, such as conducting periodic maintenance on Self-service Check -in machines, providing usage information through social media, and making efforts so that Self-service Check -in can be integrated with Self-baggage drop so that it can facilitate passengers in carrying out the Check -in process along with handling passenger baggage.